PENGEMBANGAN BUKU KERJA BERBASIS PENDEKATAN ANALOGI PADA MATA KULIAH KALKULUS II DI IAIN STS JAMBI - . relawati (Universitas Batanghari Jambi, 2017)
Developing An Analogy Approach-Based Work Book in Calculus II Subject at Institut Agama Islam Negeri Sultan Thaha Saipudin (IAIN STS) Jambi. One of the problems encountered in teaching Calculus II subject at IAIN STS Jambi was the lecture had out ye accommodated the needs of the students t study actively. Analogy approach was assumed as one of the alternative approaches which could be applied in teaching and learning process that could help the students to get involved actively. Therefore, an analogy approach-based work book was developed. The aim of this research was to develop an analogy approach-based work book which was valid. This was a developmental research which used 4-D model that consisted of defining, designing, developing and disseminating. The work book which had been developed was validated by scientists in Calculus education and language. The practicality of the book was seen through observation and questionnaire. The data gotten was analyzed descriptively. Keywords: Pendekatan Analogi, Buku Kerja Kalkulus II.